2002
DOI: 10.1074/jbc.m110516200
|View full text |Cite
|
Sign up to set email alerts
|

A Human RNA Polymerase II-containing Complex Associated with Factors Necessary for Spliceosome Assembly

Abstract: Transcription and splicing are coordinated processes in mammalian cells. We have used affinity chromatography with immobilized transcription elongation factor SII to purify a protein complex that contains core RNA polymerase II (RNA Pol II), the general transcription initiation factors, and several splicing factors, including the U1, U2, and U4 small nuclear RNPs, the U2AF 65 , and serine/arginine-rich proteins. The splicing factors and the transcription machinery co-purify through a gel filtration column and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
111
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(127 citation statements)
references
References 40 publications
14
111
1
1
Order By: Relevance
“…Association of these factors with the pol II CTD during transcription elongation would then facilitate the assembly of splicing and 3Ј-end processing complexes on nascent transcripts. Consistent with this model, several reports have described interactions between pre-mRNA processing factors and transcriptional activators (40), coactivators (41)(42)(43), and the holoenzyme (22,23). Thus, it is possible that increased splicing and cleavage levels promoted by transcriptional activators is the consequence of increased recruitment of pre-mRNA processing components to promoters.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Association of these factors with the pol II CTD during transcription elongation would then facilitate the assembly of splicing and 3Ј-end processing complexes on nascent transcripts. Consistent with this model, several reports have described interactions between pre-mRNA processing factors and transcriptional activators (40), coactivators (41)(42)(43), and the holoenzyme (22,23). Thus, it is possible that increased splicing and cleavage levels promoted by transcriptional activators is the consequence of increased recruitment of pre-mRNA processing components to promoters.…”
Section: Discussionsupporting
confidence: 50%
“…The 3Ј-end cleavage polyadenylation stimulatory factor (CPSF) interacts with the general transcription factor TFIID during transcription initiation (21), as well as with the CTD (15), indicating that it is recruited to transcription initiation complexes prior to its role in cleavage. A number of splicing or splicing-related factors have recently been detected in association with holoenzyme complexes involved in transcription initiation, further suggesting that specific pre-mRNA processing components may be recruited to active genes at the stage of transcription initiation (22,23). Recent work has also shown that the type of promoter or activator used to drive transcription can influence the level of inclusion of alternative exons in transfected pre-mRNA reporters (24 -27), suggesting that events occurring as early as promoter recognition may play an important role in the regulation of splicing.…”
mentioning
confidence: 99%
“…As a consequence, the RNAP II transcripts are efficiently directed into the spliceosome assembly pathway rather than into the inhibitory H complex. A number of spliceosomal proteins that associate with RNAP II or the CTD in vitro have been identified, including Prp40, SCAFs, PSF, p54, SR proteins and all of the spliceosomal small nuclear RNPs (snRNPs) (Mortillaro et al 1996;Yuryev et al 1996;Corden and Patturajan 1997;Kim et al 1997;Patturajan et al 1998;Morris and Greenleaf 2000;Tian 2001;Emili et al 2002;Robert et al 2002;Kameoka et al 2004;Phatnani and Greenleaf 2004), but a function for these proteins in coupling remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Their gentle technique allowed the recovery of a mixture of transcriptionally active RNAPII holoenzymes (Mr 2.4 MDa) containing all the general transcription factors from HeLa cells [12]. The protein composition of the different TFIIS-purified holoenzymes from HeLa cells was shown to consist of subunits from the spliceosome [19] and to vary according to cell cycle [22]. The changes in protein composition of TFIIS-purified holoenzymes during cell differentiation have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, RNAPII forms different holoenzymes capable of receiving and integrating cellular signals or modifing chromatin structure [13]. The diversity of complexes that interact with RNAPII span a vast spectrum of functions in transcription, genomic maintenance and splicing [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%